Tridiagonal Interval Matrix: Exploring New Perspectives and Application - Thirupathi, Sivakumar; Thamaraiselvan, Nirmala (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Tridiagonal interval matrices are relevant in diverse applications, especially in dealing with parameter estimation, optimization and circuit analysis uncertainties. This research paper aims to improve the computational efficiency of obtaining the inverse of a general tridiagonal interval matrix. This matrix is pivotal in electric circuit analysis. We achieve this by employing interval arithmetic operations in the LU decomposition process, enabling effective handling of circuit parameter uncertainties. This approach generates an inverse interval matrix that addresses uncertainties in circuit analyses.